2009
DOI: 10.1039/b914595h
|View full text |Cite
|
Sign up to set email alerts
|

Precision milled flow-cells for chemiluminescence detection

Abstract: Novel flow-cells with integrated confluence points and reaction channels designed for efficient mixing of fast chemiluminescence systems were constructed by machining opposing sides of a polymer chip and sealing the channels with transparent epoxy-acetate films. A hole drilled through the chip provided the conduit from the confluence point on one side to the centre of the reaction zone on the other side, allowing rapid presentation of the reacting mixture to the photodetector. The effectiveness of each flow-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Flow cell C was constructed by machining channels (0.7× 0.7 mm) into both faces of a polycarbonate chip (46×57×6 mm) and sealing the channels with a transparent epoxy-acetate film [20,28]. The front face contained a serpentine channel configuration, with a central entrance located above the confluence point on the back face ( Fig.…”
Section: Flow Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flow cell C was constructed by machining channels (0.7× 0.7 mm) into both faces of a polycarbonate chip (46×57×6 mm) and sealing the channels with a transparent epoxy-acetate film [20,28]. The front face contained a serpentine channel configuration, with a central entrance located above the confluence point on the back face ( Fig.…”
Section: Flow Cellsmentioning
confidence: 99%
“…For his research in these areas, he has received a Victoria Young Tall Poppy Science Award (Australian Institute of Policy and Science), the Robert Cattrall Medal (Royal Australian Chemical Institute) and the Gordon F. Kirkbright Award (Association of British Spectroscopists). machining channels into polymer materials has enabled exploration of designs that are not accessible using the traditional coiled-tubing approach [12][13][14][15][16][17][18][19][20][21]. Studies by our research group and others have shown: (1) repeated changes in the direction of solution flow (such as reversing turns) enhances the mixing efficiency and therefore the emission intensity [12,19,20,22].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…24 The effects of these factors on the CL cell are shown in Table 2. The mixing position was studied using a Pyrex spiral cell.…”
Section: Flow Cellmentioning
confidence: 99%